ASSESSING THE ROLE OF GOVERNMENT OF INDIA INITIATIVE ON PROMOTION OF INDIAN HANDICRAFTS SECTOR - Kumar, Rakesh (IJRDO - Journal of Business Management, 2016)
Indian handicrafts is an art of making crafts by hand in India is called Indian handicrafts, in ancient India people lived in colonies called tribal and they were used to make utility items for their daily need, that art of making the crafts called handicrafts, and the items called handicrafts goods. At earlier stage, Indian-handicrafts had been used as utility items to fulfill their need but now these products have become the creation of Art and are used for decorations. Time has been passed and people have become more developed and civilized in all aspects, those who were making handicraft products have started trading their makings by increasing demand and population. The government also supported them through launching of scheme. The state government of Uttar Pradesh has invited suggestions from craftsmen across the state for the formulation of the policy to improve the lives of artisans and conserve the handicraft industry. The aim of the study is to find out the role of Make in India initiatives on the handicrafts sector. This is paper is based on secondary data analysis, and explores the Government reports, the MSME reports and other secondary resources available on handicraft. We explored the status of Make in India by how much upliftment of the handicraft sector in recent past.